Evaluation of Microencapsulated Essential Oils and Organic Acids in Diets for Broiler Chickens - Zhang, K.Y.; Yan, F.; Keen, C.A.; Waldroup, P.W. (International Journal of Poultry Science, 2005)
Two experiments were conducted to evaluate the use of two products containing essential oils in diets for broiler chickens. These products were RepaXol™, a mixture of essential oils (including oregano, cinnamon, thyme, and capsicum), and Avigro™, a mixture of essential oils along with organic acids (fumaric, citric, and malic). In the first experiment, conducted in litter-floor pens, eight replicate pens of 37 male and 37 female chicks of a commercial strain were fed a non-medicated corn-soybean diet, a diet containing antibiotics (bacitracin methylene disalicylate in starter and grower and virginamycin in finisher), a diet containing 0.5 kg/ton of Avigro™, and three additional treatments utilizing RepaXol™ at 100 g/ton continuously, 00 g/ton for 0-14 d, 75 g/ton for 14-35 d; 50 g/ton for 35 to 42 d, or 150 g/ton for 0-14 d, 100 g/ton for 14-35 d; 75 g/ton for 35 to 42d. All diets were in pelleted form with starter diets crumbled. Birds were grown to 42 d. In the second experiment, eight replicate pens of five male birds housed in battery brooders were fed the negative control diet with no additives, the negative control diet with 0.5 or 1.0 kg/ton of Avigro™, or diets with RepaXol™ at 100, 200, or 300 g/ton. Diets were fed as mash. Results from the first experiment indicated no positive improvements in body weight, feed consumption, mortality, or carcass yield from addition of Avigro™ or RepaXol™. Birds fed RepaXol™ at 150 g/ton had improved feed conversion at 14 d but not over the course of the experiment. Addition of the antibiotics to the diet also had no positive improvement in live performance; however birds fed the antibiotics had a higher dressing percentage. In the second experiment, birds fed 1.0 g/ton of Avigro™ or 300 g/ton of RepaXol™, higher than suggested by the supplier, had significantly lower feed intake and significantly better feed conversion than did birds fed the negative control diet. The results of this study show some beneficial effects from the use of products containing essential oils or a mixture of essential oils plus organic acids. It appears that the response may be dose-related and that levels higher than suggested by the manufacturer may be needed to elicit this response.